Dietary omega-3 alpha-linolenic acid does not prevent venous thrombosis in mice - Reiner, Martin F.; Martinod, Kimberly; Stivala, Simona; Savarese, Gianluigi; Camici, Giovanni G.; Lüscher, Thomas F.; Wagner, Denisa D.; Beer, Jürg H. (Thrombosis and Haemostasis, 2015)
Venous thromboembolism (VTE) is a leading cause of cardiovascular death. Omega-3 fatty acids (n-3 FA) exhibit protective effects against cardiovascular disease. Others and our group have reported that the plant-derived n-3 FA alpha-linolenic acid (ALA) displays antiinflammatory, anticoagulant and antiplatelet effects, thereby reducing atherosclerosis and arterial thrombosis in mice fed a high ALA diet. Since procoagulant factors such as tissue factor and fibrin as well as platelets and leukocytes are crucially involved in the development of VTE, we investigated possible protective effects of dietary ALA on venous thrombus formation in a mouse model of stenosis- and furthermore, in a mouse model of endothelial injury-induced venous thrombosis. Four week old C57BL/6 mice underwent four weeks of high (7.3g%) or low ALA (0.03g%) treatment before being exposed to inferior vena cava (IVC) stenosis for 48 hours or laser injury of the endothelium of the internal jugular vein (IJV). Thrombus generation frequency, thrombus size and composition (IVC stenosis group) and time to thrombus formation (endothelial injury group) were assessed. In addition, plasma glycocalicin, a marker of platelet activation, platelet P-selectin and activated integrin expression as well as plasma thrombin generation was determined, but did not reveal any significant differences between he groups. Despite its protective properties against arterial thrombus formation, dietary ALA did not protect against venous thrombosis neither in the IVC stenosis nor the endothelial injury model, further indicating that the biological processes involved in arterial and venous thrombosis are different.
Keywords: Alpha-linolenic acid; cardiovascular disease; eep vein thrombosis; omega-3 fatty acids; venous thromboembolism